Antioxidant and antimicrobial activities of Sonneratia albain vitro and In vivo : comparative study with Rhizophora mucronata and Bruguiera gymnorrhiza / Md. Imdadul Haq - Md. Imdadul, Haq (2012)
The present study evaluated the antioxidant and antimicrobial potential of three mangrove species namely, Sonneratial alba, Rhizophora mucronat and Bruguiera gymnorrhiza. The bioactivities of methanol, ethanol and chloroform extracts of in vivo and in vitro explants of S. alba and in vivo explants of R. mucronata and B. gymnorrhiza were evaluated. The effects of growth regulators on seed germination of S. alba, to obtain the in vitro explants, were also studied. In the first part of bioactivity study, total phenolic contents were detected by using the Folin-ciocalteu assay. Ethanol extract of leaves of R. mucronata had the highest result for total phenolic content as 358.6 ± 0.53 mg of GAE/g of dry sample. Both enzymatic and non-enzymatic antioxidant assays were used to examine the potential of antioxidant activities of all tested samples. Ethanol and methanol extracts of barks showed better antioxidant activities compared to the leaves. Chloroform extracts in both leaf and bark samples exhibited poor antioxidant activities for all selected mangrove plants. Disc diffusion method was used to detect the antimicrobial activity of the extracts of all three plants. Two gram positive (Bacillus cereus and Staphylococcus aureus) and two gram negative (Escherichia coli and Pseudomonas aeruginosa) bacterial pathogens were used to evaluate antimicrobial activity. Methanol and ethanol extracts of leaves and barks showed promising antimicrobial activities when tested for all four abovementioned bacterial pathogens. Nevertheless, chloroform extracts exhibited poor or no antimicrobial activities against all tested microbial. Ethanol extract of barks of S. alba was fractionated into water and ethyl acetate fraction, and their antioxidant and antimicrobial activities were assessed. Water fraction exhibited better bioactive potential compared with ethyl acetate fraction. Liquid chromatography tandem mass spectrometry (LCMS/MS) analysis was also carried out with water fraction to obtain the nominal mass of the major active components in the water fraction.